Evaluation of the potential of solar chimneys to drive natural ventilation in non domestic buildings - Swainson, M. J. (Cranfield University, 1997)
The solar chimney allows natural ventilation to be achieved during periods when the wind velocities are low and the difference between internal and external air temperatures is minimal. The correct design of such building components requires that designers have appropriate design tools available to them that are both effective and easy to use. The aim of this project was to evaluate design tools currently available and if appropriate to provide a tool that would allow the effects of variations in key physical parameters to be evaluated. Two design tools are currently available to designers; zonal models and CFD programmes. Both of these were however found to be unsuitable for the evaluation of the performance of a solar chimney. Zonal models assume that the air within a zone is fully mixed which results in the effects of variations in physical parameters on the mass flow rate being incorrectly predicted. CFD programmes require validation of any models developed before confidence in the predictions can be established, it was found however that data for such validation was not available for realistic flow configurations. An experimental rig was designed and tested to ensure that the uncertainty in the data produced was both minimised and accurately quantified. A detailed review of the sensitivity of a CFD programme to model and input variables was undertaken allowing development of an appropriate model. Comparison of the results of the experimental investigation and CFD predictions showed that the CFD programme, utilising the ke turbulence model accurately predicted air flow rates through a solar chimney across a range of key physical parameter variations. Within the limits of the validity determined for the CFD model, a detailed parametric investigation was then undertaken. The result of the parametric investigation was the development of a design tool appropriate for the determination of the effects of variations of the key physical variables on the mass flow rate through a solar chimney.